ANALISIS KRITIS ATAS PELAKSANAAN INVESTASI GADAI EMAS BERTINGKAT PADA LEMBAGA KEUANGAN SYARIAH - Umardani, Dwi (Universitas Muhammadiyah Prof DR HAMKA, 2020)
This study is intended to determine the weakness points of multilevel gold pawn investment practice in Islamic financial institutions and to find out an alternative gold investment to avoid those weakness points. The research method used is a qualitative method with primary and secondary data collected through observation on Islamic financial institutions and literature review then analyzed critically and solutively. After conducting a critical analysis, it turns out that the implementation of multilevel gold pawn investment has several major weaknesses such as having to allocate certain costs to other party, there is no certainty that the price of gold will rise in the future, and the risk of loss is very high. Meanwhile, buying gold independently according to the ability of the customer then selling it and right at the moment the proceed of the sale is used to buy gold by the same size again and the next gold with smaller size in case it is done repeatedly, it can be considered as an alternative. Keywords: Multilevel gold pawn, major weakness, and alternative.